New macrostomatan snake from the Paleogene of northwestern Argentina - Albino, Adriana Maria (2018)
The lower Eocene Lumbrera Formation in Salta province, northwestern Argentina, outstands for providing snake remains from a non-Patagonian Paleogene site. The material consists of articulated precloacal vertebrae that represent a new medium-sized macrostomatan snake, namely Amaru scagliai nov. gen., nov. sp. The vertebral characters of Amaru scagliai nov. gen., nov. sp., suggest affinities with advanced clades, which is consistent with the recognition of derived macrostomatans in the early Paleocene of Bolivia and early Eocene of Brazil. The new snake confirms the presence of macrostomatan snakes in South America as early as the Eocene and suggests that the southern continents may have played an unsuspected role in the origin and evolution of advanced macrostomatans during the earliest Cenozoic.